Using Artificial Intelligence in Military Planning (Examples of GIS Software and Its Role in Military Mapping for Some Global Armies) - Muhammad, Qutaiba Raad; Khudair, Hamza Jawad (Journal of Posthumanism, 2025)
The use of Artificial Intelligence (AI) in military applications has become a prominent subject with the emergence of new methods for employing its techniques. These technologies can improve the performance of many military operations, enhance productivity and efficiency, and reduce the need for human inputs. Therefore, armies should adapt this technology according to their needs, since military dominance is no longer dependent on the size of the army but rather on the possession of effective technological tools in the military domain. Artificial Intelligence plays an increasing role in military planning and has become an essential tool in the military mapping of armies. This study highlights the uses of Artificial Intelligence in military planning and presents examples of how some global armies apply these uses within their military maps.